Calibration of ultrasound backscatter temperature imaging for high-intensity focused ultrasound treatment planning - Civale, J; Rivens, I; ter Haar, G; Morris, H; Coussios, C; Friend, P; Bamber, J (2013)
High-intensity focused ultrasound (HIFU) is rapidly gaining acceptance as a non-invasive method for soft tissue tumor ablation, but improvements in the methods of treatment delivery, planning and monitoring are still required. Backscatter temperature imaging (BTI) uses ultrasound to visualize heating-induced echo strain and may be used to indicate the position of the HIFU focal region using low-power "sub-lesioning" exposure. The technique may also provide a quantitative tool for assessing the efficacy of treatment delivery if apparent strain measurements can be related to the underlying temperature rise. To obtain temperature estimates from strain measurements, the relationship between these variables has to be either measured or otherwise assumed from previous calibrations in similar tissues. This article describes experimental measurements aimed at deriving the relationship between temperature rise and apparent strain in the laboratory environment using both exvivo bovine liver tissue samples and normothermically perfused porcine livers. A BTI algorithm was applied to radiofrequency ultrasound echo data acquired from a clinical ultrasound scanner (Z. One, Zonare Medical Systems, Mountain View, CA, USA) where the imaging probe was aligned with the focal region of a HIFU transducer. Temperature measurements were obtained using needle thermocouples implanted in the liver tissue. A series of "non-ablative" HIFU exposures giving peak temperatures below 10°C were made in three separate exvivo bovine livers, yielding an average strain/temperature coefficient of 0.126 ± 0.088 percentage strain per degree Celsius. In the perfused porcine livers at a starting temperature of 38°C (normal body temperature) the strain/temperature coefficients were found to be 0.040 ± 0.029 percentage strain per degree Celsius. The uncertainty in these results is directly linked to the precision of the strain measurement, as well as the naturally occurring variance between different tissue samples, indicating that BTI may lack the accuracy required to be implemented successfully in practice as a quantitative treatment planning technique at a sub-lesioning exposure level. This is because, to be of use in treatment planning, temperature-rise estimates may require an accuracy greater (<10%) than that offered by BTI measurement. BTI may, however, still play a role in ensuring the correct positioning of the focal region and as a treatment monitoring modality capable of detecting an increased rate of heating in tissue after HIFU ablation. © 2013 World Federation for Ultrasound in Medicine and Biology.